May Dual Transcranial Direct Current Stimulation Enhance the Efficacy of Robot-Assisted Therapy for Promoting Upper Limb Recovery in Chronic Stroke?. (December 2022) - Morone, Giovanni; Capone, Fioravante; Iosa, Marco; Cruciani, Alessandro; Paolucci, Matteo; Martino Cinnera, Alex; Musumeci, Gabriella; Brunelli, Nicoletta; Costa, Carmelina; Paolucci, Stefano; Di Lazzaro, Vincenzo
Objective: To assess whether dual transcranial direct current stimulation (tDCS) may enhance the efficacy of exoskeleton robotic training on upper limb motor functions in patients with chronic stroke. Methods: A prospective, bi-center, double-blind, randomized clinical trial study was performed. Patients with moderate-to-severe stroke (according to The National Institute of Health Stroke Scale) were randomly assigned to receive dual or sham tDCS immediately before robotic therapy (10 sessions, 2 weeks). The primary outcome was the Fugl–Meyer for Upper Extremity, assessed before, after, and at the 12-week follow-up. Neurophysiological evaluation of corticospinal projections to upper limb muscles was performed by recording motor evoked potentials (MEPs). ClinicalTrials.gov-NCT03026712. Results: Two hundred and sixty individuals were tested for eligibility, of which 80 were enrolled and agreed to participate. Excluding 14 dropouts, 66 patients were randomly assigned into the 2 groups. Results showed that chronic patients were stable before treatment and significantly improved after that. The records within subject improvements were not significantly different between the 2 groups. However, a post-hoc analysis subdividing patients in 2 subgroups based on the presence or absence of MEPs at the baseline showed a significantly higher effect of real tDCS in patients without MEPs when compared to patients with MEPs ( F  = 4.6, P  = .007). Conclusion: The adjunction of dual tDCS to robotic arm training did not further enhance recovery in the treated sample of patients with chronic stroke. However, a significant improvement in the subgroup of patients with a severe corticospinal dysfunction (as suggested by the absence of MEPs) suggests that they could benefit from such a treatment combination.